If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -93 + -14x = 150 + -5x Solving -93 + -14x = 150 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -93 + -14x + 5x = 150 + -5x + 5x Combine like terms: -14x + 5x = -9x -93 + -9x = 150 + -5x + 5x Combine like terms: -5x + 5x = 0 -93 + -9x = 150 + 0 -93 + -9x = 150 Add '93' to each side of the equation. -93 + 93 + -9x = 150 + 93 Combine like terms: -93 + 93 = 0 0 + -9x = 150 + 93 -9x = 150 + 93 Combine like terms: 150 + 93 = 243 -9x = 243 Divide each side by '-9'. x = -27 Simplifying x = -27
| x+y+25=115 | | x+12/2=13 | | 16x^2+6x=0 | | x^2=600-x | | 2(x+2)=-2(3x-1) | | 130=5(15+x) | | 1.30*40=x | | y=[x-(1+2i)][x-(1-2i)] | | 3.5x=x+5 | | (x-17)/(x-20)3 | | (2X-12)(x+5)=0 | | 10=x-4x+2 | | N=31+14 | | 10+6x=x-30 | | 3d-4=6d-11 | | x*x×x/2 | | -3n+3=27 | | n-(-130)=-2 | | 6(7-1)+8=32 | | -3x+5-7x=2-4x+3 | | Log(y)=2.5 | | =6a^3+10a^2-24a | | 2p-2/p×5p^2/7p-7 | | 4(9+5x)=36 | | 7-4x=28 | | 15-12*3= | | -3x+5-7x=2-4+3 | | k/5-4=-2 | | Y-3=1+3 | | 3(x-6)=-x+2(x-6) | | (x^2-1)(x^2+8x+12)=0 | | 49x4/7 |